PELATIHAN MICROSOFT OFFICE UNTUK PENINGKATAN KOMPETENSI KADER PKK RW 5 KELURAHAN GISIKDRONO - Arifin, Wafi (Fakultas Teknologi Informasi dan Industri Unisbank, 2025)
The PKK group has an important role in community empowerment, especially in administration and management of activities. However, many members still do not have basic skills in using Microsoft Office, which can improve their work efficiency. This training activity aims to improve the understanding and skills of PKK members of RW 5, Gisikdrono Village in using Microsoft Office, especially Microsoft Word. The training method includes material presentation, direct practice, and question and answer sessions to ensure participant understanding. The evaluation results showed that this training succeeded in improving participants' ability to process documents with good layouts and ease of use. With this training, it is hoped that PKK members can be more independent and productive in carrying out administrative tasks and social activities in their environment